2013
DOI: 10.1002/smll.201302877
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Etching in the Formation of Ag Nanoplates with Straight, Curved and Wavy Edges and Comparison of Their SERS Properties

Abstract: We investigate the role of etching in the formation of Ag nanoplates with different morphologies. By examining the reduction of AgNO3 with poly(vinyl pyrrolidone) in an aqueous solution under a hydrothermal condition, we confirm that etching plays an essential role in promoting the growth of Ag triangular nanoplates with straight edges at the expense of multiple twinned particles via Ostwald ripening. Once all the multiple twinned particles are gone, etching will continue at the corners of nanoplates, leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 39 publications
1
50
0
Order By: Relevance
“…Consistent with the results of other groups demonstrating nanoplates are superior to nanospheres for SERS [24,28], the AEF of nanoplate substrates (615 nm reduced) is at least 10 times higher than that of nanoparticles (365 nm reduced) in our results. Although Tiwari et al postulated a chemical mechanism was underlying the higher Raman signal observed with nanoplates [29], there is no evidence of differential surface absorption of particles in our experimental results, suggesting electromagnetic mechanisms may still play the dominant role.…”
Section: Surface-enhanced Raman Spectroscopysupporting
confidence: 95%
See 1 more Smart Citation
“…Consistent with the results of other groups demonstrating nanoplates are superior to nanospheres for SERS [24,28], the AEF of nanoplate substrates (615 nm reduced) is at least 10 times higher than that of nanoparticles (365 nm reduced) in our results. Although Tiwari et al postulated a chemical mechanism was underlying the higher Raman signal observed with nanoplates [29], there is no evidence of differential surface absorption of particles in our experimental results, suggesting electromagnetic mechanisms may still play the dominant role.…”
Section: Surface-enhanced Raman Spectroscopysupporting
confidence: 95%
“…8c) are difficult to visualize at this scale. Although these gaps are only approximately 15 nm, they are critical features of an effective SERS substrate [24].…”
Section: Afm Characteristicsmentioning
confidence: 99%
“…Recently, hydrothermal methods have been successfully employed in the synthesis of metal nanoplates. 61,123 For example, Yan et al prepared ultrathin triangular Ru nanoplates with a thickness of ∼3.0 nm by reducing RuCl 3 · x H 2 O with HCHO (40 wt%) in the presence of PVP at 160 °C for 4 h. 61 By simply increasing the concentration of RuCl 3 · x H 2 O and PVP, irregular-shaped ultrathin Ru nanoplates with a thickness of ∼1.5 nm were obtained. Another study showed the hydrothermal synthesis of triangular Ag nanoplates with straight and curved edges from AgNO 3 in the presence of PVP at 160 °C for 4 or 6 h. 123 …”
Section: Synthetic Methodsmentioning
confidence: 99%
“…Recently, Qin et al systematically studied the SERS activities of Ag nanoplates with straight, curved and wavy edges. 123 Compared to Ag nanoplates with straight and curved edges, those with wavy edges are richest in sharp corners and this can significantly enhance the localized electromagnetic field. As expected, the Ag nanoplates with wavy edges displayed the strongest SERS signal for 1,4-benzenedithiol molecules among the aforementioned three kinds of Ag nanoplates.…”
Section: Applicationsmentioning
confidence: 99%
“…In case of silver salt, it produced triangular Ag nanoplates with sharp and curved corners [162][163][164].…”
Section: Synthesis Of Nanoparticulate Materialsmentioning
confidence: 99%